Amylin receptor components and the leptin receptor are co‐expressed in single rat area postrema neurons. (5th February 2016) - Liberini, Claudia G.; Boyle, Christina N.; Cifani, Carlo; Venniro, Marco; Hope, Bruce T.; Lutz, Thomas A.
Abstract: Amylin is a pancreatic β‐cell hormone that acts as a satiating signal to inhibit food intake by binding to amylin receptors (AMYs) and activating a specific neuronal population in the area postrema (AP). AMYs are heterodimers that include a calcitonin receptor (CTR) subunit [CTR isoform a or b (CTRa or CTRb)] and a member of the receptor activity‐modifying proteins (RAMPs). Here, we used single‐cell quantitative polymerase chain reaction to assess co‐expression of AMY subunits in AP neurons from rats that were injected with amylin or vehicle. Because amylin interacts synergistically with the adipokine leptin to reduce body weight, we also assessed the co‐expression of AMY and the leptin receptor isoform b (LepRb) in amylin‐activated AP neurons. Single cells were collected from Wistar rats and from transgenic Fos‐GFP rats that express green fluorescent protein (GFP) under the control of the Fos promoter. We found that the mRNAs of CTRa, RAMP1, RAMP2 and RAMP3 were all co‐expressed in single AP neurons. Moreover, most of the CTRa+ cells co‐expressed more than one of the RAMPs. Amylin down‐regulated RAMP1 and RAMP3 but not CTR mRNAs in AMY+ neurons, suggesting a possible negative feedback mechanism of amylin at its own primary receptors. Interestingly, amylin up‐regulated RAMP2 mRNA. We also found that a high percentage of single cells that co‐expressed all components of a functional AMY expressed LepRb mRNA. Thus, single AP cells expressed both AMY and LepRb, which formed a population of first‐order neurons that presumably can be directly activated by amylin and, at least in part, also by leptin. Abstract : Single amylin‐activated AP neurons co‐express all necessary components of functional amylin receptors, i.e. CTRa and RAMP1, RAMP2, RAMP3, or a combination of RAMPs. The graph shows the co‐expression in CTR‐positive cells of amylin injected rats. A high percentage of these cells also co‐express the leptin receptor (LepRb). Thus, single AP‐cells form a population of first‐order neurons that presumably can be directly activated by amylin and at least in part also by leptin.